PENGARUH PENANAMAN MODAL ASING DAN PENANAMAN MODAL DALAM NEGERI TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN BERAU 2005 - 2019: PENGARUH PENANAMAN MODAL ASING DAN PENANAMAN MODAL DALAM NEGERI TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN BERAU 2005 - 2019 - Endah Susanti (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2022)
The research objective is to determine the effect of foreign investment and domestic investment on employment in Berau Regency, so that it can be used as the basis for the Berau Regency government to make work programs and policies in the future. This research uses analysis with multiple linear regression method, and the classical assumption is tested. The results of this study indicate that partially the foreign investment variable has a positive and insignificant effect on the absorption of labor in Berau Regency, and the domestic investment variable has a positive and insignificant effect on the employment of Berau Regency, and simultaneously the foreign investment and investment variables Domestic capital has a positive and significant effect on employment in Berau Regency. Simultaneously the results of this study indicate that PMDN and PMA have a positive effect on employment in Berau Regency. With a probability value of F-statistic 0.26. Partially, the regression results at the real level (α = 5%) PMDN has a significant effect on labor absorption with a coefficient of 0.438 while PMA has no significant effect on labor absorption with a coefficient of 0.381 This means that PMDN and PMA cannot make a positive contribution to absorption. manpower in Berau Regency This is because the development of PMDN and PMA in Berau Regency is still hampered by the complexity of the permit processing process due to the complicated bureaucracy and lack of integrated coordination between related departments.